2017
DOI: 10.1093/pch/pxx093
|View full text |Cite
|
Sign up to set email alerts
|

Oral health assessment practices and perceptions of North American paediatric cardiologists

Abstract: Assessments of oral health status were often deferred until immediately prior to cardiac surgery despite the cardiologist's perception that children with cardiac defects were at increased risk of oral disease and prior experience of surgical cancellation due to oral disease. Paediatricians may need to facilitate early oral assessment for these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…It was found that odontogenic pathology did not cause the development of IE in patients of the study group, and in the control group it was noted in 12.5% of patients (p = 0.01, χ 2 = 6.20). The data obtained confirm the recommendations of foreign authors on the mandatory sanitation of the oral cavity of patients before surgery on the heart and great vessels, which has been introduced into the practice of leading cardiac surgery centres in the world [7,8]. It was found that the incidence of bronchopulmonary pathology in women in the study group was 29.2% and was statistically significantly higher than in patients in the control group -11.1% (p = 0.002, χ 2 = 9.18).…”
Section: український журнал клінічної хірургіїsupporting
confidence: 83%
See 1 more Smart Citation
“…It was found that odontogenic pathology did not cause the development of IE in patients of the study group, and in the control group it was noted in 12.5% of patients (p = 0.01, χ 2 = 6.20). The data obtained confirm the recommendations of foreign authors on the mandatory sanitation of the oral cavity of patients before surgery on the heart and great vessels, which has been introduced into the practice of leading cardiac surgery centres in the world [7,8]. It was found that the incidence of bronchopulmonary pathology in women in the study group was 29.2% and was statistically significantly higher than in patients in the control group -11.1% (p = 0.002, χ 2 = 9.18).…”
Section: український журнал клінічної хірургіїsupporting
confidence: 83%
“…This can be explained by the fact that the control group included patients who underwent MV prosthetics, and therefore, valve-preserving operations were not possible in them. It is also known from the literature that oral cavity sanitation is mandatory before surgical intervention on the heart and great vessels, which is recognised and implemented in the practice of the world's leading cardiac surgery centres [7,8]. The incidence of other causes of IE in the comparative analysis between the study and control groups did not differ statistically significantly (p  0.05).…”
Section: український журнал клінічної хірургіїmentioning
confidence: 98%